Oral healthcare systems for an ageing population: concepts and challenges - Elisa M. Ghezzi (2018)
© 2017 FDI World Dental Federation Oral healthcare systems (OHCS) are designed to maintain the health and function through Communication (Health promotion and education), Prevention, Assessment and Diagnosis, and Treatment. The complexity of these OHCS functions for the ageing are described utilizing the spectrum of dependency of the Seattle Care Pathway framework. Barriers and disparities which challenge the development of OHCS for the ageing can be universal but often vary between developed and developing countries. Recognizing that oral diseases are largely preventable, strategies to improve OHCS must be targeted locally, nationally, and internationally at oral health policy, education, research, and clinical care.